Evaluation of the integrated model of the rational drug use into the Bachelor of Nursing Science program in Thailand: A mixed-methods study - Turner, Kamolrat; Suwannapong, Kanoklekha; Putthikhan, Phawida; Charoensuk, Sukjai; Radabutr, Matanee; Angsirisak, Naruemol; Thadakant, Streerut; Vaisurasingha, Laddawon; Theinpichet, Suntharawadee (Belitung Raya Foundation, Indonesia, 2021)
Background: Integration of rational drug use (RDU) into a nursing program to increase nurse graduates’ RDU competencies is essential to solving the problem of irrational drug use. Objective: This study aimed to evaluate the integrated model of the RDU into the Bachelor of Nursing Science (BNS) program developed by the Thailand Nursing and Midwifery Council (TNMC). Methods: A mixed-methods study was designed using a sequential explanatory design. The whole population of 3,848 nurse educators and 9,249 nurse graduates from 86 nursing education institutions across Thailand in Academic Year 2018 were recruited for quantitative data collection. Fifty nurse educators selected as representatives of the nursing education institutions were recruited for qualitative data collection. Online questionnaires were sent to collect information regarding the context, input, process, and product relating to the model, while structured focus group guidelines were developed to obtain more details in assessing the model. The data were analyzed using descriptive statistics and content analysis. Results: The findings showed that the context and policy of utilizing the model to increase nurse graduates’ RDU competencies were well accepted. The nurse educators’ RDU competencies, the input of the model, were rated at a high level. The process of the model was implemented as guided at almost all nursing education institutions. The product of the model, the RDU competencies of the nurse graduates, was reported at a high level. Conclusion: The model of integrating the RDU into the BNS program developed by the TNMC was well performed and resulted in high RDU competencies of the nurse graduates. This integration model should be published and applied in nursing schools worldwide to enhance RDU competencies of nurse graduates.